2-2n-2n=5n-3n

Simple and best practice solution for 2-2n-2n=5n-3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-2n-2n=5n-3n equation:



2-2n-2n=5n-3n
We move all terms to the left:
2-2n-2n-(5n-3n)=0
We add all the numbers together, and all the variables
-2n-2n-(+2n)+2=0
We add all the numbers together, and all the variables
-4n-(+2n)+2=0
We get rid of parentheses
-4n-2n+2=0
We add all the numbers together, and all the variables
-6n+2=0
We move all terms containing n to the left, all other terms to the right
-6n=-2
n=-2/-6
n=1/3

See similar equations:

| -2u+4(u+4)=20 | | 4•x+8=36 | | -1=2y+3(y-7) | | -7=-5+k | | 1.2(t-2)-6.2(t+6)=-5.3 | | `1.2(t-2)-6.2(t+6)=-5.3 | | 8y-12=4y-20 | | x/5+1.2=11.3 | | Y=x2-20x+100 | | 9x-7x=144 | | 5x-(2x-14)=36 | | x/10+10=20 | | x+4/3=6-x=1/2 | | 0.74a=490 | | 66=2(d+15) | | x/7=x/8=-12 | | 3x=3x+3=7x-14 | | -4b-6=-29 | | 5x+3x+37=180 | | 1+2p=19 | | -56=8p-8 | | 2x-(3x+4)=6x-46 | | 4a-3=15-a | | 0.3x=6.3 | | p=2(3.5+8) | | 9x^2=5x-8 | | 12n-3=4+23n | | 6(2x-1)=x-6 | | X+0.3x=1100 | | 1x-6=38 | | 7(n+4)=60 | | n8=108 |

Equations solver categories